Dominant Species in Subtropical Forests Could Decrease Photosynthetic N Allocation to Carboxylation and Bioenergetics and Enhance Leaf Construction Costs during Forest Succession - Xiao, Yihua; Liu, Shirong; Tong, Fuchun; Chen, Bufeng; Kuang, Yuanwen (Frontiers in Plant Science, 2018)
It is important to understand how eco-physiological characteristics shift in forests when elucidating the mechanisms underlying species replacement and the process of succession and stabilization. In this study, the dominant species at three typical successional stages (early-, mid-, and late-succession) in the subtropical forests of China were selected. At each stage, we compared the leaf construction costs (CC), payback time (PBT), leaf area based N content (NA), maximum CO2 assimilation rate (Pmax), specific leaf area (SLA), photosynthetic nitrogen use efficiency (PNUE), and leaf N allocated to carboxylation (NC), and to bioenergetics (NB). The relationships between these leaf functional traits were also determined. The results showed that the early-succession forest is characterized with significantly lower leaf CC, PBT, NA, but higher Pmax, SLA, PNUE, NC, and NB, in relation to the late-succession forest. From the early- to the late-succession forests, the relationship between Pmax and leaf CC strengthened, whereas the relationships between NB, NC, PNUE, and leaf CC weakened. Thus, the dominant species are able to decrease the allocation of the photosynthetic N fraction to carboxylation and bioenergetics during forest succession. The shift in these leaf functional traits and their linkages might represent a fundamental physiological mechanism that occurs during forest succession and stabilization.